The international migration of health workers. Ethics, rights and justice (Basingstoke, 2010)
"The migration of health workers from poor to richer countries is associated with important freedoms of movement and opportunity. It may also weaken critically under-staffed health systems serving poor populations and threaten their health and development goals. The medical 'brain drain' is induced by and reinforces gross global inequality and leads us to question whether health systems, migration policies and social justice are, or should be, matters of only domestic concern. The negative impacts of international health worker migration have long been lamented, but ethical analysis of the phenomenon remains scarce and ethical responses are difficult to identify."